Anisotropic model of charged spheres with double polytropic equation of state - Ashraf, Rizwana; Mardan, S. A.; Zahra, A.; Manzoor, Rubab; Inc, Mustafa (Elsevier, 2026)
In this work, we construct an exact relativistic description of a charged anisotropic compact stellar object governed by a double-polytropic equation of state. In this framework, the radial and tangential pressures obey two independent nonlinear relations with the energy density. By employing this prescription, the Einstein-Maxwell field equations are transformed into a tractable form and integrated analytically, leading to closed-form expressions for the gravitational potentials, energy density, pressure components, anisotropy factor, electric field intensity, and charge distribution. The physical viability of the model is examined through regularity requirements, positivity and monotonicity of the matter variables, causality constraints, adiabatic stability, and the standard energy conditions. The resulting solution is shown to be regular, stable, and physically acceptable throughout the stellar interior. Moreover, the double-polytropic equation of state provides greater flexibility than a linear equation of state, allowing a more effective description of ultra-dense anisotropic matter distributions in charged compact objects.
Keywords: Anisotropy; Charge; Polytropic Sphere